Respuesta :
Answer:
x = -1, y = 1
Step-by-step explanation:
Given that:
[tex]\begin{bmatrix}4x+11y=7\\ 4x+3y=-1\end{bmatrix}[/tex]
Isolate x for 4x + 11y = 7 which ⇒ [tex]x=\frac{7-11y}{4}[/tex]
Substitute [tex]x=\frac{7-11y}{4}[/tex] into the equation: which is:
[tex]\begin{bmatrix}4\cdot \frac{7-11y}{4}+3y=-1\end{bmatrix}[/tex]
Drop Down to:
[tex]\begin{bmatrix}7-8y=-1\end{bmatrix}[/tex]
Isolate y for 7-8y = -1: y = 1
Thus, [tex]x=\frac{7-11y}{4}[/tex]
Substitute y = 1
Hence,
[tex]x=\frac{7-11\cdot \:1}{4}=-1[/tex]
Solution ⇒ x = -1 and y = 1
~learn with lenvy~
Answer:
x = -1 , y = 1
Step-by-step explanation:
Starting with x
x = 7 - 11y/4
4 × 7-11y/4 + 3y = -1
7 - 8y = -1
Now for y
7-8y = -1 ⇒ y = 1
Hence, x = -1 and y = 1
[RevyBreeze]